Children’s game songs and rhymes - Matiure, Perminus; Matiure, Rungamirai (African Journal of Children’s literature, 2019)
The article presents and discusses children’s game songs (mitambo yevana) usually performed during children’s play time. Each game song is transcribed and discussed to unpack the role the game plays in developing certain skills and concepts in children. The article is a follow up of an applied action research carried out at Chemhanza Mission on Hwedza District of Mashonaland East province of Zimbabwe. Children are products of the social fabric whose social experiences are woven within the nexus of social webs generated by social power vested in the social system. One way in which children develop physically, intellectually, socially and morally skills is through playing games that are accompanied by either rhymes or songs. The games discussed in this article are motsiro, zai rakaora, vana vana huyai, sarura wako, kana ndikadayi, chamutswinye mutswinye,chitima, chinyunyunyu, sapero, and maringoringo.